Sea bass hatchery operations. - Parazo, MM; Garcia, LMB; Ayson, FG; Fermin, AC; Aaalmedras, JME; Reyes, DM; Avila, EM (Aquaculture Department, Southeast Asian Fisheries Development Center, 1990)
Aquaculture Extension Manual No. 18; July 1990